A switch and a failsafe: KatG’s mechanism for preservation of catalase activity using a conformationally dynamic Arg and an active-site Trp - Xu, Hui; Kenneson, Jessica R.; Minton, Laura E.; Goodwin, Douglas C. (Frontiers in Chemical Biology, 2024)
Many novel structural features impart a robust catalase activity to KatG that is absent from all other members of its superfamily. The conformationally dynamic “Arg switch” and oxidizable “proximal Trp” have both figured prominently in investigations of KatG structure and mechanism, but the full scope of their contributions to catalysis remains unclear. The switch (R418) appears to regulate active-site intramolecular electron transfer. The proximal Trp (W321) is a conspicuous site of radical formation, but W321•+ does not appear to participate directly in the KatG catalase cycle. To explore the extent to which these residues may cooperate in KatG’s catalase activity, we generated R418N and W321F/R418N KatG and compared their catalytic and spectroscopic properties to wt KatG. R418N KatG showed pH-independent susceptibility to H2O2-based inactivation, whereas wt KatG only showed this response under conditions where the Arg switch would be oriented away from the active site (i.e., low pH). Peroxidatic electron donors (PxEDs) prevented inactivation of wt and R418N KatG regardless of pH; however, protection of R418N KatG activity by this mechanism produced at least ten-fold greater extents of PxED oxidation. Elimination of the proximal Trp in addition to the Arg switch (i.e., W321F/R418N KatG) resulted in a near complete inability to sustain H2O2 degradation. Remarkably, W321F KatG showed resistance to H2O2-dependent inactivation indistinguishable from wt at pH 7 (i.e., when the Arg switch is oriented toward the active site) but sensitivity to H2O2-dependent inactivation indistinguishable from W321F/R418N KatG at pH 5 (i.e., when the Arg switch is oriented away from the active site). These data suggest loss of the Arg switch (either by mutagenesis or conformationally due to environmental pH) results in a KatG that is substantially compromised in the sustained degradation of H2O2. This can be overcome provided that KatG retains its ability to utilize the proximal Trp as a site of protein-based oxidation and has a PxED available to repair protein oxidation events. However, if both the Arg switch and the proximal Trp are absent, rapid H2O2-dependent inactivation is observed, and PxEDs are unable to effectively intervene to preserve KatG’s catalase activity.